Mediating role of goal setting in the relationship between situational leadership and work intentions in Jordan - Al-Khamaiseh, Zaydoon Dhafi
One of the main challenges facing Jordan Telecommunication Sector (JTS) companies is predicting Work Intentions of their workers, and keeping their best staff satisfied and loyal for extended retention period. Many employees switched to other local or regional organizations annually. Hence, examining factors that could retain them from switching to another service provider is of great importance. A few previous studies showed the Situational Leadership SL, and the Goal Setting (OS) as one of the core organizational theories that may influence employee satisfaction, loyalty, and predicting their Work Intentions WI. This research managed to explore the mediating role of (OS) on the association concerning SL and middle managers WI. Besides, it investigated the relationship between SL ® and WI of middle managers in (JTS) companies. A quantitative research method was employed, and nine experts and two practitioners pretested the survey using a self-administered questionnaire and applied a pilot study of 100 participants. Overall, it has targeted a population of 450 participants in (JTS), where the unit of analysis was the middle manager position in the three leading telecommunication companies providing telephone and internet services. The survey was distributed online to a sample of 320 participants selected using the stratified simple random sampling through their official email addresses, where 280 participants adequately responded to the study after three email reminders sent to them by the HR department of each company during one month of data collection. Exploratory Factor Analysis EF A was used to examine the pilot study, Confirmatory Factor Analysis CF A was applied to examine the constructs' validity, and the Structural Equation Modeling SEM was employed to test the research hypotheses, utilizing IBM-SPSS 25.0 and AMOS 24.0. The main findings of this study revealed that SL ® didn't have a significant effect on WI directly, SL had a considerable impact on (OS) instantly, and (OS) had a substantial effect on WI directly. n the other hand, SL influenced WI through the mediator (OS). Besides, the study revealed that participants applied the four components of SL. The research revealed the existence of a direct impact of SL on (OS), and an immediate effect of (OS) on WI, while an indirect effect of SL ® on WI existed when (OS) is considered a mediator. As far as the theoretical implication is concerned, the study is a premier study that integrates the SL theoretically with (OS) and WI in one model for telecommunication industry services in Jordan. This research also provided a better understanding of how companies and decision-makers should apply SL and (OS) in their management activities in terms of improving their Work Intentions, reducing their turnover, and increasing their retention period in their current organizations.